Debt Financing And Firm Performance: An Analysis Of Securities Commission Of Malaysia 2013 Revised Shariah Approved Firms Screening Method - Nurshamimitul Ezza Ramli; Gairuzazmi M Ghani; Razali Haron; Norazizan Che Embi (Comsat University Islamabad, 2024)
This study aims to assess the impact of Securities Commission (SC) of Malaysia 2013 revised Shariah approved firms screening method in relation to the levels of debt and the Shariah- approved firms’ performance. Panel regressions were employed to examine the impact for firms that are consistently Shariah-approved as determined by the SC of Malaysia.The period of study is 2000 to 2014. There gression result indicatesa non-monotone association between Shariah-approved firms’ performance and debt levels. The optimum level of debt, however, is much higher than the 33% benchmark set by SC. Hence, it can be concluded that the 2013 revised Shariah- approved firms screening method which introduced the 33% debt ratio benchmark did not improve the performance of Shariah-approved firms for the period studied. Nevertheless, since the observations are only until 2014, it is possible that the observations have not capture the true impact of the change.